Rock art of the Vindhyas : an archaeological survey : documentation and analysis of the rock art of Mirzapur District, Uttar Pradesh - Pratap, Ajay, (Archaeopress, 2016)
How does rock art as an object fashioned by human hands then differ from tools? What utility does it have beyond its symbolic value? The Vindhyan corpus of rock paintings has provided us with a very valuable opportunity to be answering such questions.